Exploring the patient perspectives of student‐resourced service delivery of rehabilitation groups: A qualitative study. (30th November 2021) - Pigott, Amanda; Patterson, Freyr; Prescott, Sarah; Doig, Emmah; Fleming, Jennifer
Abstract: Introduction: Occupational therapists commonly use groups to deliver rehabilitation. Previous research has established that patients value participation in such groups. With increasing demands for rehabilitation services, meeting the intensity of occupational therapy practice required for recovery is challenging. Group‐based services are one approach to support increased rehabilitation need for intensity of practice. Student‐resourced service delivery (SRSD) of rehabilitation groups is a novel practice placement model that shows potential for rehabilitation care delivery. There is little research reporting patient experiences and perspectives of SRSD rehabilitation groups. Understanding the perspectives of patients' experiences of the groups is required for meaningful programme evaluation. This study aimed to explore patient experiences of SRSD of rehabilitation groups. Methods: This multisite qualitative study examined the perspectives of 26 rehabilitation inpatients participating in SRSD group sessions across two rehabilitation sites. The SRSD group sessions were overseen by an occupational therapist. Data were collected through semi‐structured interviews and analysed using inductive thematic analysis guided by a phenomenological approach. Results: Three themes emerged: (1) seeing the relevance of SRSD groups, (2) enhancing the process of SRSD groups, and (3) the value of social interaction. Conclusion: SRSD rehabilitation groups were well received by patients with perceived benefits such as opportunities for social interactions. Findings from this study may inform clinical practice including models of student practice placement education.